2008
DOI: 10.1590/s0103-84782008000900003
|View full text |Cite
|
Sign up to set email alerts
|

Novas características para diferenciação de cultivares de soja pela análise discriminante

Abstract: INovas características para diferenciação de cultivares de soja pela análise discriminante New traits for differentiation of soybeans using discriminant analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 1 publication
4
20
0
5
Order By: Relevance
“…Due to the economic importance, the cultivation of soybean (Glycine max (L.) Merrill) is one of the crops with greatest increase in planted area and the agribusiness segment in Brazil (Nogueira et al 2008). Soybean and its derivatives are highly promising raw material for the food industry, especially in cereal and meat-based products.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the economic importance, the cultivation of soybean (Glycine max (L.) Merrill) is one of the crops with greatest increase in planted area and the agribusiness segment in Brazil (Nogueira et al 2008). Soybean and its derivatives are highly promising raw material for the food industry, especially in cereal and meat-based products.…”
Section: Introductionmentioning
confidence: 99%
“…Nogueira et al (2008) and Matsuo et al (2012) also identified variability in CH, EC, and CPFT CRFT among genotypes, in four different periods of seeding. Furthermore, Nogueira et al (2008) reported large genetic influence for most of the characteristics in different periods, showing little environmental effect. The repeatability coefficients for the CH, ranged from 0.369 to 0.705.…”
Section: Resultsmentioning
confidence: 88%
“…Currently, about 38 descriptors are used between the mandatory and the additional to differentiate genotypes of soybean, nevertheless, they are still insufficient to distinguish cultivars (Nogueira et al, 2008). Therefore, there is the need of expanding that list.…”
Section: Introductionmentioning
confidence: 99%
“…According to Nogueira et al (2008), the 38 descriptors, including the additionals descriptors used to differentiate cultivars of soybean are insufficient, which points out to the need of broadening the list of these descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…According to Nogueira et al (2008), there is genetic variability for the lengths of hypocotyl and epicotyl in the germplasm of soybean. Studies subsequent to this were carried out in order to estimate the genetic variability of the lengths of hypocotyl and epicotyl and for a better understanding of these characteristics (Matsuo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%